Monitoring the cost and affordability of a healthy diet within Countries: Building systems in Ethiopia, Ghana, Malawi, Nigeria, Pakistan, Tanzania, and Viet Nam - Herforth, Anna Whitson; Gilbert, Rachel; Sokourenko, Kristina; Fatima, Tehreem; Adeyemi, Olutayo; Alemayehu, Dawit; Arhin, Eunice; Bachewe, Fantu Nisrane; Bai, Yan; Chiosa, Imran; Genye, Tirsit; Haile, Hagos; et al. (Elsevier, 2024)
Background Governments around the world collect food price data on a frequent basis, often monthly, for the purpose of monitoring inflation. These routine economic data can be used with a nutrition-sensitive lens for understanding economic access to a healthy diet. The United Nations Food and Agriculture Organization has adopted the cost and affordability of a healthy diet (CoAHD) for annual tracking alongside other food security indicators. This indicator is relevant in many countries for informed decision-making and accountability toward food systems summit pathways. National governments may wish to include this indicator in their own monitoring systems, using existing subnational price and income data. Objectives We describe emerging systems in several countries for monitoring CoAHD and analytical tools that facilitate the calculation of CoAHD. We discuss reasons why the indicator may differ when calculated using subnational data compared with the global monitoring system and how to interpret differences. Methods Between June 2016 and February 2024, 19 workshops were held in 7 countries (Ethiopia, Ghana, Malawi, Nigeria, Pakistan, Tanzania, and Viet Nam), where stakeholder discussions covered sources of food price data, institutions involved, policy uses, and direct training in calculation of CoAHD. Food price data collected by national organizations were used to calculate CoAHD in partnership with government agencies. Results Calculating CoAHD using subnational data uses the same methods across settings, but the mechanisms for monitoring and dissemination are different in each country, illustrating heterogeneity in how the metric can most effectively be incorporated within existing structures. Results from national and global monitoring systems have expected differences based on data sources, healthy diet standards, and affordability standards. Conclusions CoAHD can be calculated with existing data and resources, facilitated by new software tools and user tutorials. In the future, it can be further streamlined, leveraging technical assistance from global institutions and aligning national and global monitoring systems.